2013
DOI: 10.4103/0028-3886.125264
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex and inflammatory cell subtype expression in inflammatory myopathies and muscular dystrophies

Abstract: The pattern of MHC-I and II expression appeared to be similar in both inflammatory myopathies as well as in muscular dystrophies with inflammation and hence differentiating them on MHC - I expression was difficult.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
(39 reference statements)
0
7
0
Order By: Relevance
“…Nagappa et al, also demonstrated that, in patients with IIMs, the MHC class-I was upregulated along the membrane of all muscle fibers. 1 Some of the inflammatory cells were labeled with MHC class-I in the endomysium and perimysium, whereas sarcoplasmic staining was not identified in any muscle fibers including the regenerating and necrotic fibers. 1 …”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Nagappa et al, also demonstrated that, in patients with IIMs, the MHC class-I was upregulated along the membrane of all muscle fibers. 1 Some of the inflammatory cells were labeled with MHC class-I in the endomysium and perimysium, whereas sarcoplasmic staining was not identified in any muscle fibers including the regenerating and necrotic fibers. 1 …”
Section: Introductionmentioning
confidence: 88%
“…The major histocompatibility complex (MHC) class-I antigen is an integral membrane glycoprotein normally expressed in all nucleated cells. 1 In human, normal muscle tissue does not express MHC class-I and the expression is usually seen in normal endomysial capillaries. 1 MHC class-I plays an important role in both initiating and continuing the muscle damage.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations